Police legitimacy - M. P. Kleymenov; M. V. Sedeltsev (Правоприменение)
The subject of the article is assessment of public confidence in the police and the legality of its activities by the opinion of the Russian population. The purpose of the research is to identify the reasons that affect the assessment of the police legitimacy, its perception by the population. The authors also dare to identify the role of "problem areas" of police activity (related to different violations of the law) in people assessment.The methodology of the research includes: sociological survey among Russians, comparative criminological, statistical, hermeneutic methods, expert assessments.The main result, scope of applications. The central link of the police legitimacy is public trust, recognition, leading to the cooperation between the people and the authorities. Legitimacy assessments are formed based on the study of public opinion – the official monitoring procedure. The website of the Russian Ministry of Internal Affairs provides information on the results of monitoring public opinion about the activities of the police, but an analysis of its content allows us to note its superficiality and unconvincing optimism. This is obviously affected by the shortcomings of the departmental legal regulation of the process of monitoring public opinion about the activities of the police, which, judging by the questionnaire questions (there are only three of them), is rather imitative in nature. We believe that the official monitoring of public opinion on the activities of the police, at a minimum, should be supplemented by the results of independent sociological studies aimed at establishing "problem areas" of police activity related to violations of the law, violence, ill-treatment, provocations, inducing someone, directly or indirectly, to commit illegal actions, other official abuses. Otherwise, the regulatory requirements for the activities of the police, which establish the foundations of its legitimacy, cannot be fully implemented. The survey of 362 citizens conducted by the authors allows to state that, with a fairly high assessment of the activities of the Russian police, respondents pay attention to the existence of such problems as: the lack of transparency of police activities and the presence of formal and informal means of evading the legality of police activity, the tolerance of justice authorities to police lawlessness, intoxication with power by police officers, the impact of police brutality on social and legal despair, violation of the law in the name of achieving its falsely understood goals. The extreme case of perverted official zeal is the execution of illegal orders. There are quite widespread ideas in public opinion that entrepreneurs often become victims of extortion by the police, that the police take bribes from medium and small businesses, that you can buy off police officers. At the same time, the results of the study indicate that a significant part of the population is determined to cooperate with the police.Conclusions. The public demand for the police is relevant, the honor and main meaning of which is to protect the interests of all people and serve justice. People need such policemen who will demonstrate not strength and power, but simple human complicity. This is the main secret of the legitimacy of the police. Another secret lies in the orientation of personnel policy towards professionals in the police: their selection, training and support in difficult situations.